Image of ethnic integration in Malaysian children novels - Muhayat, Faezah; Muhamad Affendi, Nik Rafidah Nik; Kamarudin, Kamariah (International Journal of Scientific and Technology Research, 2020)
Ethnic integration is the process of uniting various racial groups in society through the introduction and creation of a common identity. Literature is one of the mediums that can serve as a vehicle for ethnic integration in society especially among children. This paper discusses the image of ethnic integration among Malaysians that are featured in children's novels. This study is based on literature reviews which found that research on ethnic integration in Malaysian literary works is largely focused on adult literature rather than on children's literature. Therefore, studies on ethnic integration in children's novels should be given attention so that the reading material offered is not only enjoyable but able to provide knowledge and educate through its content, fostering a sense of unity among the children in the Malaysian multi-ethnic society. To achieve the stated objectives, this study focuses on an award-winning children‟s novel, the recipient of Novel and Drama Scriptwriting Competition for Children and Teen (9-12 Years Old Category) by Dewan Bahasa dan Pustaka, a book entitled Gerbang Pelangi (Rainbow Gate) by Rohaidah Yon as the research text.This qualitative study uses the literary review and text analysis as the methodology of the study by utilizing J. S. Furnivall's Theory of Plural Society (1948) as the analytical framework. Findings of the study show that the novel can enhance the ethnic integration of the Malaysian community through social interaction and peacefulness featured in the plot.